Strategi Peningkatan Hasil Prestasi Siswa pada Tes Kompetensi Akademik(TKA) Tingkat Madrasah Aliyah di Rembang - Mukhoyaroh Mukhoyaroh; Heldy Ramadhan Putra (CV. ALIM'SPUBLISHING, 2026)
Academic achievement is a key indicator in assessing the success of the educational process, one measure of which is the Academic Competency Test (TKA). Achieving optimal TKA results requires well-planned and sustained learning strategies, in which teachers play a central role in their design. This study aims to describe teachers’ strategies for improving student performance on the Academic Competency Test (TKA). This study employs a qualitative approach with a descriptive design. The research subjects are teachers, with data collected through interviews, observations, and document analysis. The results indicate that teachers implement six main strategies, namely: (1) strengthening TKA-based curriculum through the integration of content and the development of questions based on analysis and critical thinking; (2) conducting intensive practice programs in the form of specialized tutoring, practice exercises, and mock tests; (3) enhancing teacher competencies through training in the development of Higher-Order Thinking Skills (HOTS)-based questions and the application of innovative learning models such as problem-based learning and inquiry-based learning; (4) utilization of technology through the use of learning applications, e-learning platforms, and analysis of learning outcome data; (5) student guidance and support through academic mentoring, supplementary classes, and counseling services; and (6) enhancement of student learning motivation through the provision of continuous support. The findings of this study indicate that strategies systematically designed and implemented by teachers can improve students’ academic and mental readiness for the Academic Competency Test (TKA). Therefore, teachers play a crucial role in optimizing learning strategies to enhance students’ academic achievement.